Лесные тайнички: рассказы / Н. И. Сладков - Сладков Николай Иванович (АСТ, 2008)
Экземпляры: Д. б. (20220803) / Инвентарный номер: 42271 / Цена: 131.67 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 72 / ББК: 84(2Рос=Рус)6-4